Feasibility of Physics Teaching Materials With Qur'an Using Generative Learning Model on Sound Waves - Muhammad Lutfi; Zainuddin Zainuddin; Eko Susilowati (Berkala Ilmiah Pendidikan Fisika, 2021)
Preliminary observations show the limitations of teaching materials that have a relationship with spiritual aspects, especially the Qur'an, which is due to the limitations of teaching materials that contain these aspects. Required learning that stimulates students to generalize religious aspects and learn physics. Therefore, the purpose of this study is to describe the feasibility of physics teaching materials containing the Qur'an by using a generative model on sound wave material. This study aims to describe the validity, practicality, and effectiveness of the teaching materials developed. The research was conducted on 33 students at class XI MIPA 1 MAN 2 Model Banjarmasin using the ADDIE model. Data was taken from the validation results of teaching materials using validation sheet, lesson plan implementation using lesson plan implementation sheet, and students' learning outcomes at the pretest and post-test using learning outcomes tests. The results of this study were 1) the validity of the teaching materials was in the "valid" category with a value of 3.33, 2) the practicality of the teaching materials was in the "very practical" category with a value of 3.63, and 3) the effectiveness of the teaching material was in the "effective/moderate" category with a value of 0,44. This study concluded that physics teaching materials containing Al-Qur'an verses on sound wave materials using generative learning models are declared feasible to be used based on the validity, practicality, and effectiveness of the teaching materials. The implication of this research is the creation of teaching materials containing the Qur'an that are used in schools and creating student habits to link physics and the Qur'an.